Pengaruh Persepsi Tentang Kualitas Jasa Pendidikan dan Kepemimpinan Kepala Sekolah terhadap Kepuasan Peserta Didik di SMA XYZ Bogor - Setiawati, Irene (Jurnal Ketopong Pendidikan, 2023)
Customer Customer satisfaction has become a crucial concern for many organizations, as it directly influences the sustainability and success of the business. Similarly, in the educational context, student satisfaction plays a vital role in determining a school’s reputation, competitiveness, and long-term development. Schools are expected to provide high-quality educational services and effective leadership to ensure that students’ academic and personal needs are met. This study aims to examine the influence of educational service quality and the school principal’s leadership on students’ satisfaction. The research was conducted at XYZ Christian High School in Bogor, involving 135 students as respondents. Using a quantitative approach, the data were analyzed with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method supported by the PASW software. The findings reveal that students’ perceptions of educational service quality and principal leadership have a significant positive effect on their satisfaction. Furthermore, the study also found that the principal’s leadership positively influences students’ perceptions of educational service quality. These results suggest that effective school leadership contributes not only to better service quality but also to higher student satisfaction, which is essential for maintaining the school’s overall performance and competitive advantage.